Genetic tools for metabolic engineering of Pichia pastoris - Wu, Xiaoyan; Cai, Peng; Yao, Lun; Zhou, Yongjin J (Engineering Microbiology, 2023)
The methylotrophic yeast Pichia pastoris (also known as Komagataella phaffii) is widely used as a yeast cell factory for producing heterologous proteins. Recently, it has gained attention for its potential in producing chemicals from inexpensive feedstocks, which requires efficient genetic engineering platforms. This review provides an overview of the current advances in developing genetic tools for metabolic engineering of P. pastoris. The topics cover promoters, terminators, plasmids, genome integration sites, and genetic editing systems, with a special focus on the development of CRISPR/Cas systems and their comparison to other genome editing tools. Additionally, this review highlights the prospects of multiplex genome integration, fine-tuning gene expression, and single-base editing systems. Overall, the aim of this review is to provide valuable insights into current genetic engineering and discuss potential directions for future efforts in developing efficient genetic tools in P. pastoris. [Display omitted]